2017
DOI: 10.1515/pjct-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and genotoxicity of GO-Fe3O4 hybrid in cultured mammalian cells

Abstract: The study was aimed at investigating the effect of the Fe 3 O 4 hybrid deposited on graphene oxide (GO-Fe 3 O 4 ) on the relative viability and DNA integrity. The properties of the GO-Fe 3 O 4 hybrid were analyzed using a transmission electron microscopy (TEM), X-ray diffraction technique (XRD) and thermal gravimetric method (TGA), while the effi ciency of graphene oxide covalent functionalization with iron oxide nanospheres was determined by Fourier transform infrared spectroscopy (FT-IR). L929 and MCF-7 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The main PC parameters measured in the reviewed articles were thickness, lateral size, zeta potential, and hydrodynamic diameter. However, although not so commonly, other parameters such as surface area [ 54 , 55 , 56 ], chemical composition [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], impurity concentration [ 56 , 57 , 63 , 64 , 67 , 68 ], aggregation/agglomeration [ 54 , 60 , 63 , 64 , 69 , 70 ], morphology and/or surface characteristics [ 55 , 57 , 71 , 72 ], thermal stability [ 67 ], elasticity [ 56 ], precipitation in suspension [ 65 ], number of layers [ 54 , 57 , 60 , 61 , 63 , 64 , 71 , 73 , 74 , 75 , 76 , 77 ] hydrophobicity [ …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main PC parameters measured in the reviewed articles were thickness, lateral size, zeta potential, and hydrodynamic diameter. However, although not so commonly, other parameters such as surface area [ 54 , 55 , 56 ], chemical composition [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], impurity concentration [ 56 , 57 , 63 , 64 , 67 , 68 ], aggregation/agglomeration [ 54 , 60 , 63 , 64 , 69 , 70 ], morphology and/or surface characteristics [ 55 , 57 , 71 , 72 ], thermal stability [ 67 ], elasticity [ 56 ], precipitation in suspension [ 65 ], number of layers [ 54 , 57 , 60 , 61 , 63 , 64 , 71 , 73 , 74 , 75 , 76 , 77 ] hydrophobicity [ …”
Section: Resultsmentioning
confidence: 99%
“…A total of six publications analyzed MN formation after exposure to GBMs [ 58 , 63 , 64 , 65 , 66 , 78 ] ( Table 1 ). Most of these publications used the conventional CBMN assay for this purpose, but a flow cytometer-based method using the MicroFlow Kit (Litron, Rochester, NY) was also performed in the study by Petibone et al, 2017 [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mounting literature indicated that the GO coupled with magnetic nanoparticles could serve as a potential material for the diagnosis and treatment of cancers ( Chen H. et al, 2021 ). Currently, several researches reported various methods to synthesize magnetic and graphite nanostructured composites (Fe 3 O 4 /GO) for catalytic, water purification, biomedical diagnostic, and therapeutic applications ( Jedrzejczak-Silicka, 2017 ; Yan et al, 2019 ; Niu et al, 2021 ; Sadighian et al, 2021 ). This combination of topical hyperthermia materials is also regarded as a promising candidate for drug delivery ( Karimi and Namazi, 2021 ; Wen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%